(untitled) (Al-Academy, 2017)
The expressive speech in the art of acting is considered to be the leading action for thinking and the interior interaction of the individual, in the organization of his relationship with the elements of the environment and its content, and the more acquired the individual’s performance today skills in organizing and export of his conflicts and natural occasions , whenever , becomes more adaptable and an interpreted physically and acoustically inside pluralities in personalities, suited to the modern age. This research has addressed a range of topics related to expressive speech in the art of acting, since the first chapter included a systematic framework of the research, represented by the problem , the importance and aims of research to detect speech expressionist being a need for cultural environments and address of societies and civilizations. The second chapter, it was within the theoretical framework, represented by the following axes: (concept of speech, the concept of expression, and expression in the art of acting). While the third chapter included a description of analytical personality, being a part of the subject of discourse in the expressionist art of acting, and reached a number of conclusions and made a number of recommendations and suggestions and finally research ended with a list of sources